PCSK9 potentiates innate immune response to RNA viruses by preventing AIP4-mediated polyubiquitination and degradation of VISA/MAVS - Han Fang; Mengling Shi; Cong Wang; Saiting Zhang; Na Kong; Mengyao Ji; Yan Wang; Yidan Zhou; Qiyun Zhu; Yu Zhang; Shishen Du; Shuai Xu; et al. (Proceedings of the National Academy of Sciences, 2025)
Upon viral infection, retinoic acid-inducible gene-I (RIG-I)-like receptors (RLRs) detect viral RNA to initiate antiviral innate immune response, which is mediated by the mitochondrial adaptor protein VISA virus-induced signaling adaptor; also known as mitochondiral antiviral-signaling protein (MAVS). The stability and activity of VISA are tightly regulated by various posttranslational modifications, among which polyubiquitination plays important roles. Various E3 ubiquitin ligases, including atrophin interacting protein 4 (AIP4), mediate polyubiquitination of VISA and result in its degradation. However, how polyubiquitination of VISA is regulated remains unclear. Here, we uncovered a dual function for proprotein convertase subtilisin/kexin type 9 (PCSK9), a key enzyme in cholesterol homeostasis and a well-known therapeutic target in cardiovascular diseases, modulating host responses to RNA viruses both extracellularly and intracellularly. Secreted PCSK9 inhibited sendai virus (SeV) and vesicular stomatitis virus (VSV) infection, while the intracellular PCSK9 potentiated RLRs-mediated interferons (IFNs) induction by stabilizing VISA on mitochondria. Viral infection induced the translocation of PCSK9 to mitochondria where it competed with AIP4 for VISA, thereby inhibiting its polyubiquitination and degradation. Consequently, overexpression of PCSK9 enhanced VISA-mediated innate immune response against RNA viral infection, whereas its deficiency had the opposite effects and resulted in more robust replication of the virus. Pcsk9 −/− mice produced lower levels of type I IFNs and proinflammatory cytokines, rendering the increased sensitivity to VSV and influenza A virus infection. Altogether, our findings uncovered an important and unexpected role of PCSK9 in virus–host interaction and contribute to the understanding of the sophisticated mechanism governing the proper and efficient immune response to viral infection.